2013
DOI: 10.1126/scitranslmed.3007148
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Induces Adipose Dysfunction in Vivo Through Reciprocal Effects on PPAR/GR Co-Regulation

Abstract: Viral infections, such as HIV, have been linked to obesity, but mechanistic evidence that they cause adipose dysfunction in vivo is lacking. We investigated a pathogenic role for the HIV-1 accessory protein viral protein R (Vpr), which can coactivate the glucocorticoid receptor (GR) and co-repress peroxisome proliferator–activated receptor γ (PPARγ) in vitro, in HIV-associated adipose dysfunction. Vpr circulated in the blood of most HIV-infected patients tested, including those on antiretroviral therapy (ART) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 50 publications
7
82
0
Order By: Relevance
“…Viral infections have been linked to obesity and hepatic steatosis in other diseases [29,30]. A murine model suggested that viral protein R, released from HIV-1 in tissue reservoirs after ART treatment, produces adipose dysfunction and hepatosteatosis through alterations in cell cycle signaling [31]. This may partially explain a more direct role of HIV infection on obesity, and account for the continued occurrence of metabolic changes among virally suppressed persons.…”
Section: Discussionmentioning
confidence: 93%
“…Viral infections have been linked to obesity and hepatic steatosis in other diseases [29,30]. A murine model suggested that viral protein R, released from HIV-1 in tissue reservoirs after ART treatment, produces adipose dysfunction and hepatosteatosis through alterations in cell cycle signaling [31]. This may partially explain a more direct role of HIV infection on obesity, and account for the continued occurrence of metabolic changes among virally suppressed persons.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, co-culture of preadipocytes with CD4+ T cells harboring latent HIV virus increases the preadipocyte IL-6 expression nearly 3-fold (44). Together, these findings suggest an adverse cycle in which local cytokines potentiate viral shedding and activation of latently-infected adipose tissue CD4+ T cells, and these CD4+ T cells may then in turn increase expression of pro-inflammatory mediators from adipocytes via paracrine signaling pathways, leakage of viral proteins such as Vpr or Tat (discussed below), or other mechanisms (2, 57, 102, 237). …”
Section: Adipose Tissue Immunology and Hiv Infectionmentioning
confidence: 95%
“…While advances in pharmacologic options for HIV treatment have reduced the incidence and severity of ART-induced adipocyte toxicity (principally mitochondrial DNA [mtDNA] depletion and altered gene expression), the persistence of viral proteins in circulation and locally within adipose tissue impairs adipocyte maturation and activity despite suppression of plasma viremia on therapy (2, 7, 29, 57, 163, 186, 196, 236, 260). More recently, the identification of latently-infected CD4+ T cells in adipose tissue has emerged as an important consideration for HIV cure research, and a potential source of chronic adipose tissue immune activation and inflammation via cytokine production and viral protein shedding (2, 43, 44, 47, 198). In this review, we provide a synthesis of the literature on how HIV virus, ART treatment, and host characteristics interact to affect adipose tissue distribution and contribution to metabolic health, adipose tissue immunology, and adipocyte maturation, cellular regulation, and energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it seems that adipose-specific metabolic defects in PLWH undergoing cART treatment could directly contribute to lymphoma risk via increases in circulating leptin. Moreover, a number of direct effects of HIV accessory proteins on adipocyte functions have been described in animal models [67,68] and human cells [69-71] many of which could contribute to the induction of a lymphoma-promoting chronic inflammatory state.…”
Section: Adipose Tissue Reservoirs and Implications For Lymphomamentioning
confidence: 99%